Adaptive deep brain stimulation for Parkinson's disease: closed loop stimulation for Parkinson's. - Little, S (2014)
Our understanding of the pathophysiology Parkinson’s disease has transformed over the last decade as we have come to appreciate the importance of changes in neuronal firing pattern that occur within the motor network in the dopamine deficient state. These changes in firing pattern, particularly increased synchrony result in oscillations that can be recorded as local field potentials. This thesis concerns itself with the study of beta oscillations which are characteristic of Parkinson’s disease. Firstly, I investigate whether beta oscillations play a pathophysiological role in Parkinson’s disease or whether they are purely epiphenomenal by augmenting beta with low frequency deep brain stimulation. In this study I show that rigidity is increased by ~25% with low frequency stimulation providing significant further evidence for a patho-physiological role of beta in Parkinson’s disease. Next I investigate whether beta oscillations correlate with Parkinsonian severity at rest and could therefore potentially be used as a biomarker of clinical state. I demonstrate that the variability of beta amplitude recorded from the subthalamic nucleus strongly correlates with symptom severity at rest and also in response to levodopa administration. I then use beta amplitude as a biomarker for a trial of adaptive deep brain stimulation in Parkinson’s disease. I show that by using beta amplitude to control stimulation, time on stimulation is reduced by >50% but despite this, clinical outcome is improved by 25% relative to conventional continuous high frequency stimulation. Finally, I investigate the bilateral subcortical beta network and its response to levodopa. I report statistically significant bilateral functional connectivity in the beta range which is driven by phase locking and modulated by levodopa in the low beta range with implications for bilateral adaptive deep brain stimulation. These findings further our understanding of the pathophysiological role of beta oscillations in Parkinson’s disease and provide new avenues for treatment development.